2023
DOI: 10.1038/s41392-023-01528-y
|View full text |Cite
|
Sign up to set email alerts
|

Methylation across the central dogma in health and diseases: new therapeutic strategies

Ruochen Liu,
Erhu Zhao,
Huijuan Yu
et al.

Abstract: The proper transfer of genetic information from DNA to RNA to protein is essential for cell-fate control, development, and health. Methylation of DNA, RNAs, histones, and non-histone proteins is a reversible post-synthesis modification that finetunes gene expression and function in diverse physiological processes. Aberrant methylation caused by genetic mutations or environmental stimuli promotes various diseases and accelerates aging, necessitating the development of therapies to correct the disease-driver met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 811 publications
0
5
0
Order By: Relevance
“…DNA methylation plays an important role in regulating gene expression, especially those occur in the gene promoter regions ( 6 , 16 ). Therefore, we sought to explore whether the altered expression of CYR61 in BRCA is related to its promoter methylation level.…”
Section: Resultsmentioning
confidence: 99%
“…DNA methylation plays an important role in regulating gene expression, especially those occur in the gene promoter regions ( 6 , 16 ). Therefore, we sought to explore whether the altered expression of CYR61 in BRCA is related to its promoter methylation level.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that OTU domain(1–180aa) is the main catalytic domain of OTUD4. However, studies reported that the deubiquitase recruitment domain (DRD, 181–550aa) of OTUD4 interacts with and deubiquitinates ALKBH3 [ 41 , 42 ], intrinsically disordered regions (IDRs, such as 885–1114aa) of OTUD4 interacts with RNA [ 43 ], the ubiquitin interaction motif (UIM, 271–300aa) of OTUD4 promotes its DUB activity against MyD88 [ 10 ]. Similarly, in our study, 301–550aa of OTUD4 is the catalytic domain for deubiquitination of CDK1, and 181–300aa of OTUD4 might promote the DUB activity of OTUD4 on CDK1 by enhancing their interaction ability.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, health care providers should also consider assessing the expression of PMTs when determining combinational drug regimens for individual cancer patients. Moreover, Liu et al highlight how the use of methylation editing technologies can alter histone methylation marks to change the expression of target genes [ 23 ]. Thus, gene regulation can be an attractive therapeutic strategy that targets specific cancer cell populations with long-lasting effects.…”
Section: Discussionmentioning
confidence: 99%
“…While it is widely recognized that dysregulation in protein methylation contributes to cancer formation and progression, further research is essential to identify driver methylation targets in a cancer-specific context that can be used for diagnosis, screening, monitoring, and prognosis purposes [ 23 ]. This study aims to uncover the roles of PMTs in EMT in CRC to explore whether these PMTs contribute to a poorer prognosis in CRC.…”
Section: Introductionmentioning
confidence: 99%